2014
DOI: 10.1155/2014/479584
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Supplemented Revascularization of an Immature Tooth Associated with a Periapical Lesion in a 40-Year-Old Man

Abstract: The present case report is the first of its kind that documents the successful outcome of “revascularization,” a regeneration-based treatment protocol in a mature adult patient. It belies the myth that “revascularization” should only be done in children and young, adolescent patients. The misconception that stem cells number as well as viability in older age group patients will not allow revascularization to be successful is also contradicted by this case. The paper highlights all the mechanisms that come into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…15 The effectiveness of PRP in improving the biological outcome of regeneration/revitalisation protocols has been tested in many studies, and it has been used instead of a blood clot for endodontic regeneration/revitalisation cases; however there is considerable variation in the outcomes reported. 8,[16][17][18] This may be due either to variations in the platelet product preparation method, for example the preparation of lysate/glue/fibrin membrane/scaffold, or variation in the platelet concentration in these preparations. Some research has shown that a high concentration of platelets could have an adverse effect on human dental stem cell and bone cell proliferation and differentiation, 19,20 and that PRP is only effective at specific concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…15 The effectiveness of PRP in improving the biological outcome of regeneration/revitalisation protocols has been tested in many studies, and it has been used instead of a blood clot for endodontic regeneration/revitalisation cases; however there is considerable variation in the outcomes reported. 8,[16][17][18] This may be due either to variations in the platelet product preparation method, for example the preparation of lysate/glue/fibrin membrane/scaffold, or variation in the platelet concentration in these preparations. Some research has shown that a high concentration of platelets could have an adverse effect on human dental stem cell and bone cell proliferation and differentiation, 19,20 and that PRP is only effective at specific concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, blood venous derivatives, such as PRP (Jadhav et al . , , , Guven Polat et al . , Bezgin et al .…”
Section: Resultsmentioning
confidence: 99%
“…In such a context, EDTA has been suggested to be applied in RCR as it can solubilize the growth factors fossilized in the dentine matrix (Graham et al 2006), which seems to be essential for pulp regeneration (Conde et al 2016). However, only 14 from the selected studies applied EDTA during RCR (Paryani & Kim 2013, Soares et al 2013, Alobaid et al 2014, Amit et al 2014, Jadhav et al 2014, Lei et al 2015, McCabe 2015, Nevins & Cymerman 2015, Ray et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…From these, 38 studies met the inclusion criteria of the present study. Forty-five studies were excluded after full-text reading once they did not report the color maintenance or the tooth discoloration (23-62), or since the tooth discoloration described had occurred prior to revascularization procedure (63)(64)(65)(66)(67)(68).…”
Section: Studies Selectionmentioning
confidence: 99%